The relationship between seismic velocity, mineral composition and temperature and pressure in the upper mantle—with an application to the Kenya Rift and its eastern flank - Mechie, James; Fuchs, Karl; Altherr, Rainer (Tectonophysics, 1994)
Using the elastic properties of individual minerals the velocity of a rock at a known temperature and pressure can be calculated. Alternatively, from P- and/or S-wave seismic velocities at a particular depth (pressure and temperature) the mineralogical composition of a rock may be estimated. In this study, this procedure is applied to the uppermost mantle beneath the Kenya Rift and its eastern shoulder. It will be shown that, for estimated in-situ temperatures and pressures, the mineralogical compositions derived from mantle xenoliths found on the eastern shoulder are compatible with the uppermost-mantle Pn velocities derived from the KRISP 90 seismic experiment beneath the eastern shoulder. Here the Pn velocities are compatible with an average undepleted spinel peridotite composition at temperatures of 300-400°C, corresponding to surface heat flows of 35-50 mW/m2, at 30-35 km depth and in certain areas with a composition containing a 10-15% increase in olivine at temperatures of 600-670°C, corresponding to a surface heat flow of about 75 mW/m2, at 30-35 km depth. Beneath the Rift itself, where no mantle xenoliths have been found, the mineralogical composition derived from mantle xenoliths found on the eastern shoulder is not compatible with the low observed uppermost-mantle Pn velocities of 7.5-7.7 km/s. Under both the northern Rift and the southern Rift where Moho temperatures of respectively 630°C at 21 km depth (5.6 kbar) and 1000°C at 35 km depth (9.6 kbar) have been estimated, corresponding in both cases to a surface heat flow of 105-120 mW/m2, the observed Pn velocities are 0.1-0.3 km/s lower than the predicted velocities. In order to explain these low observed velocities, the presence of 3-5% basaltic melt rising from greater depths and being trapped just below the Moho is invoked. At depths greater than those penetrated by the Pn-wave, for the northern Rift a temperature-depth profile of 830°C at 35 km depth (10.0 kbar), 940°C at 45 km depth (12.9 kbar), 1030°C at 55 km depth (16.0 kbar) and 1100°C at 63 km depth (18.4 kbar) has been used, while for the southern Rift values of 1200°C at 45 km depth (12.9 kbar), 1300°C at 55 km depth (16.0 kbar) and 1350°C at 63 km depth (18.4 kbar) have been utilized. Beneath the southern Rift the observed low velocities which are less than 7.8 km/s, can again be explained by the presence of basaltic melt which probably exists as in-situ partial melt below 45 km depth. The high-velocity layers beneath the northern Rift with velocities of 8.05-8.15 km/s at a high estimated temperature of about 940°C at 45 km depth and about 8.3 km/s at a high estimated temperature of about 1100°C at 60-65 km depth require some kind of preferred mineral orientation. Possible models include either a transverse isotropic structure in which the slow b-axis of olivine is oriented vertically and the faster a- and c-axes are randomly oriented in the horizontal plane or an orthorhombic structure in which some 40-55% of the olivine has the fast a-axis oriented horizontally along the rift axis. In the case of the layer at 60-65 km depth, if a transverse isotropic structure exists, then depletion of basalt may additionally be required in order to reconcile the observed and predicted seismic velocities.